Trashy town - Zimmerman, Andrea Griffing; Clemesha, David; Yaccarino, Dan ([New York] : HarperCollinsPublishers, 1999)
Little by little, can by can, Mr. Gillie, the trash man, cleans up his town.
Keywords: Refuse and refuse disposal -- Fiction